AIRE in Male Fertility: A New Hypothesis - Petrusová, Jana; Manning, Jasper; Filipp, Dominik (Cells, 2022)
Male infertility affects approximately 14% of all European men, of which ~44% are characterized as idiopathic. There is an urgency to identify the factors that affect male fertility. One such factor, Autoimmune Regulator (AIRE), a protein found in the thymus, has been studied in the context of central tolerance functioning as a nuclear transcription modulator, responsible for the expression of tissue-restricted antigens in specialized thymic cells that prevent autoimmunity. While its expression in the testes remains enigmatic, we recently observed that sterility in mice correlates with the absence of Aire in the testes, regardless of the deficient expression in medullary thymic epithelial cells or cells of the hematopoietic system. By assessing the Aire transcript levels, we discovered that Sertoli cells are the exclusive source of Aire in the testes, where it most likely plays a non-immune role, suggesting an unknown mechanism by which testicular Aire regulates fertility. Here, we discuss these results in the context of previous reports which have suggested that infertility observed in Aire deficient mice is of an autoimmune aetiology. We present an alternative point of view for the role of Aire in testes in respect to fertility altering the perspective of how Aire's function in the testes is currently perceived.
Keywords: Animals; autoimunita; buněčné jádro; Cell Nucleus; fertilita; zvířata; mužské pohlaví; Autoimmunity; Epithelial Cells; Fertility; Male; Mice; epitelové buňky; myši